1946
DOI: 10.1152/ajplegacy.1946.146.1.61
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Responses to the Breathing of 100 Per Cent Oxygen at Normal Barometric Pressure

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

1948
1948
1966
1966

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 0 publications
5
22
0
Order By: Relevance
“…(6). This was subsequently confirmed by numerous other workers (7)(8)(9)(10). Alella and Meda, in 1948, reported that this effect on heart rate was not present in atropinized subjects (11).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…(6). This was subsequently confirmed by numerous other workers (7)(8)(9)(10). Alella and Meda, in 1948, reported that this effect on heart rate was not present in atropinized subjects (11).…”
supporting
confidence: 76%
“…At least three independent groups reported decreases in cardiac output in normal subjects breathing oxygen as estimated by ballistocardiograph-decreases averaging 8 to 10 per cent and largely due to decreased heart rate (5,8,20 (21).…”
mentioning
confidence: 99%
“…In four of these, blood pressure increased by 3-8 % and in the remainder it fell by a similar amount. The changes observed in this series are of the same order as those reported in adult man breathing 100 % oxygen at one atmosphere (Dautrebande & Haldane, 1921;Whitehorn, Edelmann & Hitchcock, 1946;Dripps & Comroe, 1947;Eggers, Paley, Leonard & Warren, 1962 Filled circles indicate steady-state points when the lamb breathed air and 3.5 % C02 in air; open circles, */PA CO2 when the lamb breathed 100 % oxygen and 3.5 % C02 in 02. The figures indicate P2,02 at these points and the arrows the change in 1V and PAXC2 from ambient to high PI,02 at the two levels of inspired C02.…”
Section: Normal Values and Controlssupporting
confidence: 67%
“…Such a decrease could be due to: 1) a reduction in the volume of blood flow through the pulmonary vascular bed, 2) a diminution of pulmonary vascular resistance, or 3) a fall of the left atrial and pulmonary venous pressure. A decrease in cardiac output during oxygen breathing in man has been noted by several investigators using the ballistocardiograph (12)(13)(14). This decrease has been estimated to be from 10%o to 20%o and is reflected initially by a decrease in pulse rate.…”
Section: Discussionmentioning
confidence: 90%
“…This decrease has been estimated to be from 10%o to 20%o and is reflected initially by a decrease in pulse rate. It has been reported that during the first five minutes of oxygen breathing, approximately 94%o of the decrease in cardiac output is reflected in a decrease of pulse rate and the remainder is reflected by a decrease of stroke output (12). Although there is some question regarding the validity of absolute values for cardiac output as determined by the ballistocardiograph, it seems likely that the changes in output observed during oxygen breathing by this method are valid.…”
Section: Discussionmentioning
confidence: 99%